2015
DOI: 10.1007/s12034-015-0936-6
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity and mechanical behaviour of cobalt oxide-doped bioactive glass

Abstract: Bioactive glasses are materials capable of bonding implants to tissues. 45S5 Bio-glass R is one such material capable of bonding strongly to bone within 6 weeks. It develops a hydroxy-carbonate apatite layer on the implant that is chemically and crystallographically equivalent to the mineral phase of bone. However, it suffers from a mechanical weakness and low fracture toughness due to an amorphous glass network and is not suitable for load-bearing applications. In order to improve its mechanical strength and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 30 publications
3
25
0
Order By: Relevance
“…The authors found that there was an excellent agreement between metal-oxygen (M-O) correlation obtained for Ni by isotopic substitution and Ni/Co data sets by isomorphic substitution method which confirmed that both Ni 2+ and Co 2+ ion were isostructural in the bioactive glasses. [4,39,40] in an earlier investigation had also shown that the addition of cobalt oxide up to 2.0 wt% in 45S5 bioactive glass-ceramic has resulted in an increase in density and compressive strength of their samples due to formation Co-O-Si bonds. Azevedo et al [26] had also performed the 29 Si MAS-NMR to determine the role of Co 2+ ion in the silicate glass structure and reported the dual role of Co 2+ as an intermediate and modifier in their bioglass samples depending upon its concentration like Mg 2+ , Ca 2+ and Zn 2+ ions.…”
Section: Fig 5 -Ftir Of the Bioactive Glass-ceramic (Nio-1c) Before mentioning
confidence: 99%
“…The authors found that there was an excellent agreement between metal-oxygen (M-O) correlation obtained for Ni by isotopic substitution and Ni/Co data sets by isomorphic substitution method which confirmed that both Ni 2+ and Co 2+ ion were isostructural in the bioactive glasses. [4,39,40] in an earlier investigation had also shown that the addition of cobalt oxide up to 2.0 wt% in 45S5 bioactive glass-ceramic has resulted in an increase in density and compressive strength of their samples due to formation Co-O-Si bonds. Azevedo et al [26] had also performed the 29 Si MAS-NMR to determine the role of Co 2+ ion in the silicate glass structure and reported the dual role of Co 2+ as an intermediate and modifier in their bioglass samples depending upon its concentration like Mg 2+ , Ca 2+ and Zn 2+ ions.…”
Section: Fig 5 -Ftir Of the Bioactive Glass-ceramic (Nio-1c) Before mentioning
confidence: 99%
“…Kokubo and his teams developed Simulated Body Fluid (SBF) which has similar inorganic ion concentrations to those of human extracellular fluid 22,[29][30][31] . The ion concentrations of SBF are given on Table. 2.…”
Section: Simulated Body Fluid (Sbf)mentioning
confidence: 99%
“…12 2+ and Na + ions from the sample surface 22,23,25,26 . The sample number G-4 with higher zirconia content was found to show maximum pH value may be due to high rate of dissolution as compared to base sample G-1.…”
Section: Ph Performance In Simulated Body Fluidmentioning
confidence: 99%
See 2 more Smart Citations